Bacteriophage Therapeutics: A Primer for Clinicians on Phage‐Antibiotic Combinations. Issue 2 (13th January 2020) - Morrisette, Taylor; Kebriaei, Razieh; Lev, Katherine L.; Morales, Sandra; Rybak, Michael J.
Abstract : Multidrug‐resistant organisms have caused a marked depletion of effective antimicrobials, and the narrow pipeline of antibiotics has demanded the need to find novel therapeutic alternatives including nonantibiotic agents. Bacteriophages (phages) are viruses that use the bacterial machinery to infect, replicate, and kill bacterial cells. Although a marked decline in their use was driven by the discovery of antibiotics, the era of antibiotic resistance has led to a resurgence of phage therapy into clinical practice. The term phage‐antibiotic synergy (PAS) was coined just over a decade ago and described that sublethal concentrations of antibiotics could stimulate phage production by bacterial cells. Recent literature has described PAS and other encouraging interactions with various phage and antibiotic combinations against a variety of bacterial strains. The primary objective of this review is to discuss the positive interactions between phage and antibiotic combinations, with an emphasis on PAS, reductions in bacterial growth or minimum inhibitory concentrations, enhanced biofilm eradication, and alterations in the emergence of bacterial resistance. A peer‐reviewed literature search was conducted (1890–2019) using the PubMed, Medline, and Google Scholar databases. Although more investigation is certainly needed, the combination of bacteriophages with antibiotics is a promising strategy to target organisms with limited or no therapeutic options. This approach may also foster the ability to lower the antibiotic dose and may reduce the potential for antibiotic resistance emergence during therapy.